2011
DOI: 10.4097/kjae.2011.61.6.470
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the humidifier on sore throat and cough after thyroidectomy

Abstract: BackgroundThis study was performed to determine the effects of a humidifier with heated wire circuits on the incidence and severity of postoperative sore throat (POST) and cough after thyroidectomy.MethodsA total of 61 patients scheduled for elective thyroid surgery under general anesthesia were included in this prospective study. We randomized the patients in to two groups, "without active warming and humidification" (Group C) and "using a heated humidifier" (Group H). The patients were interviewed to obtain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 17 publications
2
49
0
Order By: Relevance
“…One of the main ndings in the current study was that postoperative cough was relatively common after thyroid surgery, with an overall prevalence rate of 28.5%, and it was more common in patients with malignant disease than in patients with benign disease. In a study by Jung et al [17], the authors aimed to determine the effects of a humidi er with heated wire circuits on the prevalence and severity of cough after thyroidectomy, and they reported that in patients undergoing active humidi cation of inspired gases, the prevalence of postoperative cough was signi cantly decreased compared to patients without a heated humidi er. In the current study, all patients had routine postoperative aerosol inhalation of budesonide aerosol and ambroxol, twice a day for 5 days.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main ndings in the current study was that postoperative cough was relatively common after thyroid surgery, with an overall prevalence rate of 28.5%, and it was more common in patients with malignant disease than in patients with benign disease. In a study by Jung et al [17], the authors aimed to determine the effects of a humidi er with heated wire circuits on the prevalence and severity of cough after thyroidectomy, and they reported that in patients undergoing active humidi cation of inspired gases, the prevalence of postoperative cough was signi cantly decreased compared to patients without a heated humidi er. In the current study, all patients had routine postoperative aerosol inhalation of budesonide aerosol and ambroxol, twice a day for 5 days.…”
Section: Discussionmentioning
confidence: 99%
“…Cool and dry anaesthetic gas reaches the airways directly during the mechanical ventilation following endotracheal intubation. In this case, a reduction to be seen in the temperature and humidity of respiratory tracts (2,5,6). When the humidity level of respiratory tracts goes down below a certain value, mucus decreases.…”
Section: Introductionmentioning
confidence: 97%
“…Surgery and nursing care of thyroid gland, which is an important endocrine organ due to its functions, anatomic placement and neighborhood, requires a special knowledge and proficiency (1). Although thyroidectomy is one of the operations, which are frequently performed with a low mortality rate today, it may cause severe morbidity, bleeding, recurrent damage of neuronal and parathyroid glands and problems such as laryngeal edema (2,3). Pain is one of the early signs of these problems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations